Anxiety-Related Frontocortical Activity Is Associated With Dampened Stressor Reactivity in the Real World. (June 2022) - Hur, Juyoen; Kuhn, Manuel; Grogans, Shannon E.; Anderson, Allegra S.; Islam, Samiha; Kim, Hyung Cho; Tillman, Rachael M.; Fox, Andrew S.; Smith, Jason F.; DeYoung, Kathryn A.; Shackman, Alexander J.
Negative affect is a fundamental dimension of human emotion. When extreme, it contributes to a variety of adverse outcomes, from physical and mental illness to divorce and premature death. Mechanistic work in animals and neuroimaging research in humans and monkeys have begun to reveal the broad contours of the neural circuits governing negative affect, but the relevance of these discoveries to everyday distress remains incompletely understood. Here, we used a combination of approaches—including neuroimaging assays of threat anticipation and emotional-face perception and more than 10, 000 momentary assessments of emotional experience—to demonstrate that individuals who showed greater activation in a cingulo-opercular circuit during an anxiety-eliciting laboratory paradigm experienced lower levels of stressor-dependent distress in their daily lives ( n s = 202–208 university students). Extended amygdala activation was not significantly related to momentary negative affect. These observations provide a framework for understanding the neurobiology of negative affect in the laboratory and in the real world.